Reflecting on Pipes’s and Brzeziński’s works : Vittorio Strada and the nature of totalitarian dictatorships - Berti, Francesco (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
Vittorio Strada, one of the most distinguished Italian scholars of 19th- and 20th-century Russian literature and political history, formulated his final interpretation of the Russian revolution and its internal stages, the relationship between Marx, Lenin and Stalin’s thought, the concept of totalitarianism and the troublesome comparison between Nazism and communism between the 1980s and the 1990s. Expanding upon Richard Pipes’s thesis about the preservation of a czarist, authoritarian spirit and corresponding institutions in the Soviet state and Brzeziński’s and Friedrich’s refinement of the well-known concept of totalitarianism, Strada perfected his own interpretation of Soviet communism and in turn made it more useful to analyze totalitarian systems and ideologies.
Keywords: Vittorio Strada; Richard Pipes; Zbigniew Brzeziński; concept of totalitarianism